Analisis Formulasi Dan Evaluasi Tablet Effervescent - Herta Meidya Nurhalita; Miftakhul Jannah; Alfi Dwi Seviah; Vina Aprilia Safari; Natalia Abuk Bria; Ria Lestari Herawati; Ramadhan Maulana Putra; Yani Ambari; Dewi Rahmawati; Marthy Meliana Ariyanti Jalmav; Muhammad Fithrul Mubarak (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
The purpose of writing this review article is to determine the formulation analysis and evaluation of the use of various additional ingredients in effervescent tablets. The method used is a literature review originating from journals and other research results from various references regarding the formulation and evaluation of additional ingredients in various types of effervescent tablets. This aims to provide a summary of relevant publications and increase current understanding. Formulation and evaluation of additional ingredients in effervescents are important aspects that need to be considered in product development. Decisions regarding the use of additives should be based on the desired purpose, desired physical characteristics, stability, and consumer acceptability. With a good understanding of the formulation and evaluation, high quality effervescent tablets can be produced. The use of a variety of additional ingredients can provide different taste and texture characteristics to effervescent, which can affect consumer acceptability.